Identitas Muslimah dan Hijab: Kajian Tafsir Al- Qur’an Pada Surah An- Nur dan Al- Ahzab - Marsha, Agil Rizkya; Azzahra, Khairunnisa; Pakpahan, Meliana; Tarigan, Mhd Rafi’i Ma’arif (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the tendency to simplify the meaning of the obligation to wear the hijab in society, where this obligation is understood only as a physical covering and disregards the ethical and social aspects mandated by the Quran. The main objective of this research is to examine the essence and scope of the hijab through an interpretation of Surah An-Nur verse 31 and Al-Ahzab verse 59, in order to formulate an ideal implementation framework that is adaptive to modern challenges. The method used is qualitative, focusing on an in-depth literature review of the Quran, tafsir works (especially Al-Misbah and Ibn Kathir), and academic literature. The findings indicate a close relationship between personal ethics (khimar, Ghadul Bashar) and self-representation in public spaces (jilbab). It is concluded that a complete Muslim woman's identity requires complete harmony between the visual manifestation of the hijab and internal moral integrity, where moral values must be the primary foundation of one's appearance. This research contributes to presenting a conceptual model of Islamic law regarding the limitations and nature of the hijab to support moderate religious practices.